83.4k views
1 vote
-15 + 12x = 5x + 7 -3x
SOLVE FOR X

User Brae
by
4.4k points

2 Answers

3 votes

Answer:
x=(11)/(5)

Simplify both sides of the equation


-15+12x=5x+7+-3x


12x-15=(5x+-3x)+(7) (Combine Like Terms)


12x-15=2x+7

Subtract 2x from both sides


12x-15-2x=2x+7-2x\\10x-15=7

Divide both sides by 10


(10x)/(10) =(22)/(10)


x=(11)/(5)

User Tcollart
by
5.0k points
1 vote

Answer:


x = 2.2

Explanation:


- 15 + 12x = 5x + 7 - 3x \\ + 12x - 5x + 3x = 15 + 7 \\ 10x = 22 \\ (10x)/(10) = (22)/(10) \\ x = 2.2

User Benmcredmond
by
5.1k points